Descriptive analysis of students' self-control in learning and the aspects that influence it - Sano, Afrizal; Sariro, Sariro; Zola, Nilma (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2022)
Having good self-control, especially in learning, is an important thing that every student needs to have. Self-control, which is a part of inhibitory control, is the ability to restrain one's emotions, thoughts, and actions in the face of temptations and impulses. Self-control is a cognitive process that is required for controlling one's behavior in order to accomplish particular goals, and it is classified as an executive function.With good self-control, students will have the ability to control the impulses that exist within themselves and from others. This study aims to analyze students’ self-control in learning and the aspects that influence it. The method used is descriptive quantitative, with a research population of 720 students, then by using a stratified random sampling technique, a research sample of 108 students was obtained. The data analysis technique used is descriptive analysis. The results showed that students’ self-control based on aspects of discipline, prudence, healthy habits, work ethics and consistency were still in the moderate category, so it can be concluded that students’ self-control still needs to be improved. So that school counselors need to provide services to students who need help.